GE_GERICHTE P/20701/2010 vom 13. Dezember 2021 - GE Cour de justice (2021)
QUALITÉ POUR AGIR ET RECOURIR;DOMMAGE;INDEMNITÉ(EN GÉNÉRAL);CONFISCATION(DROIT PÉNAL);CRÉANCE;ALLOCATION AU LÉSÉ | CP.138; CPP.115; CPP.122; CO.51; CO.144; CP.70; CP.71; CP.73; CPP.433